Methoxpropamine (MXPr) in powder, urine and hair samples: Analytical characterization and metabolite identification of a new threat. (April 2022) - Goncalves, R.; Castaing, N.; Richeval, C.; Ducint, D.; Titier, K.; Morvan, E.; Grélard, A.; Loquet, A.; Molimard, M.
Highlights: First identification of MXPr in France with analytical findings. Identification of new psychoactive substances requires combined methods such as RMN, IR and HRMS. N-despropyl(nor)MXPr, O-desmethyl MXPr and dihydroMXPr are relevant metabolites for MXPr identification. Abstract: Methoxpropamine (MXPr) is an arylcyclohexylamine dissociative drug with structural similarities with 3-MeO-PCE, ketamine and deschloroketamine. MXPr was identified for the first time in Europe in October 2019 in Denmark and is considered a new psychoactive substance. We undertook the molecular identification and characterization of MXPr in urine, hair and powder samples. We used a combination of several analytical methods: liquid-state nuclear magnetic resonance (NMR), infra-red spectroscopy (IR) and liquid chromatography high-resolution mass spectrometry (LC-HRMS). The second objective was to explore the metabolism of MXPr in silico and in vitro. To detect characteristic metabolites that prove MXPr consumption by urine analysis, pooled human liver microsome (pHLM) assays were performed and evaluated using liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QToF-MS). A software algorithm (Unifi®) was used to predict in silico biotransformations of MXPr. Three metabolites were identified in the in vitro studies including N-despropyl(nor)MXPr, O-desmethyl MXPr and dihydroMXPr. Most of these phase II metabolites were confirmed to be present in urine and hair samples collected from an MXPr consumer. This is the first report of the identification of MXPr in France with analytical findings. This study highlights the challenge of identifying new psychoactive substances (NPS) when they are missing from compound libraries and if a standard is not available. The use of various complementary analytical methods combined with HRMS offers a promising approach for the molecular characterization of NPS.